Evaluating SAARC : Challenges and Opportunities for Regional Cooperation in Recent years - Islam, MD. Rafiul; Afia Jahin Jerin; Mst. Afsana Afrin; Tanvir Ahmed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
SAARC, the South Asian Association for Regional Cooperation, was formed in 1985 to build cooperation among South Asian countries and improve life for people across the region. Over the years, SAARC has worked on issues like poverty, trade, education, health, and disaster management. But despite these efforts, progress has often been limited by political tensions especially between India and Pakistan and by weak institutional structures. Still, SAARC has had some success and holds great promise for the future. This research explores how SAARC is structured, what it has achieved so far, the challenges it faces, and the opportunities it still has to become a stronger force for development and peace in South Asia.